ILOKANO MOTHERS’ LIVED EXPERIENCES AND MEANING-MAKING IN MULTILINGUAL CHILD-REARING: NEGOTIATING ENGLISH AND ILOKANO IN EARLY CHILDHOOD - Maxene Janel Batangan; Ryan Roi Domingo (SEAQIL Journal of Language Education, 2026)
This phenomenological study explored the lived experiences and meaning-making processes of Ilokano mothers as they navigate multilingual parenting in the context of their children’s early childhood English language learning. Ten purposively selected Ilokano mothers participated in semi-structured interviews, and the data were analyzed using Colaizzi’s phenomenological method adapted within an interpretive framework. Findings revealed that mothers’ language practices were shaped by caregiving responsibilities, family relationships, digital media exposure, schooling experiences, and community interactions. Mothers negotiated English and Ilokano as complementary languages with distinct social and emotional meanings: English was associated with confidence, educational opportunities, social mobility, and imagined futures, while Ilokano was connected to cultural identity, emotional belonging, and intergenerational relationships. The findings further revealed that mothers’ language decisions were influenced by their personal histories, social expectations, and aspirations for their children’s linguistic futures. Rather than viewing multilingualism as a choice between competing languages, mothers interpreted multilingual practices as a way of supporting children’s adaptability, social connection, and cultural continuity. The study contributes to understanding multilingual motherhood by highlighting how language learning in early childhood is a relational and identity-driven process shaped by family practices, cultural negotiation, and everyday experiences. These insights provide implications for educators, families, and policymakers in supporting bilingual development while sustaining heritage languages in multilingual communities.